HSD17B4, ACAA1, and PXMP4 in Peroxisome Pathway Are Down-Regulated and Have Clinical Significance in Non-small Cell Lung Cancer - Zhang, Xiuzhi; Yang, Hongmei; Zhang, Jinzhong; Gao, Fenglan; Dai, Liping (Frontiers in Genetics, 2020)
To explore the potential functions and clinical significances of peroxisomes during lung cancer development and progression, we investigated the expressional profiles of peroxisome pathway genes and their correlations with clinical features in non-small cell lung cancer (NSCLC). The RNA-seq data of NSCLC including lung squamous carcinoma (LUSC) and lung adenocarcinoma (LUAD) patients with their clinical information were downloaded from The Cancer Genome Atlas (TCGA). Gene expression comparisons between tumor and normal samples were performed with edgeR package in R software and the results of the 83 peroxisome pathway genes were extracted. Through Venn diagram analysis, 38 common differentially expressed peroxisome pathway genes (C-DEPGs) in NSCLC were identified. Principal components analysis (PCA) was performed and the 38 C-DEPGs could discriminate NSCLC tumors from the non-tumor controls well. Through Kaplan-Meier survival and Cox regression analyses, eleven of the C-DEPGs were shown to have prognostic effects on NSCLC overall survival (OS) and were considered as key C-DEPGs (K-DEPGs). Through Oncomine, Human protein atlas (HPA) and the Clinical Proteomic Tumor Analysis Consortium (CPTAC), three K-DEPGs (HSD17B4, ACAA1 and PXMP4) were confirmed to be down-regulated in NSCLC at both mRNA and protein level. Their dy-regulation mechanisms were revealed through their correlations with their copy number variations and methylation status. Their potential functions in NSCLC were explored through their NSCLC-specific co-expression network analysis, their correlations with immune infiltrations, immunomodulator gene expressions, MKI67 expression and their associations with anti-cancer drug sensitivity. Our findings suggested that HSD17B4, ACAA1, and PXMP4 might be new markers for NSCLC diagnosis and prognosis and might provide new clues for NSCLC treatment.